Pandangan Islam Terhadap Globalisasi: Analisis Tafsir Maudui - Syamil, Al Fikru; Zayyan, Firasfatika; Ar Razi, Humaira; Pebriani, Naila; Muhyi, Asep Abdul (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This paper discusses Islam and globalization, utilizing a qualitative method through a descriptive-analytical and thematic (maudhui) interpretation approach. The data used are qualitative in nature, non-numerical, with the primary source being the Quran, and secondary sources including literature related to the research topic such as books, classical texts, articles, journals, and other references. The reality of globalization has a significant impact on individuals in their daily lives. The appropriate response to this phenomenon should be wise and cautious. Islam is a universal and global religion that plays a role in addressing the challenges of globalization. The universality of Islam demonstrates its profound influence on the future of the world. This universality can be seen in various aspects such as its cosmopolitan cultural teachings, holistic social structure, and scientific advancement. Islam also possesses the capacity to address issues in the fields of economy, technology, education, and other areas.Islam strongly emphasizes that Muslims should not fall into imitation or rejection in the negative context of globalization. Instead, it aligns with Islamic values, tolerance, and understanding of real-world conditions, thereby teaching how to act wisely and objectively.